Technical and Vocational Education and Training Fund in Nepal: Present Practice and Way Forward (Journal of Training and Development, 2021)
In the last few decades, Technical and Vocational Education and Training (TVET) expanded significantly in Nepal. However, the actors of TVET are uncoordinated and are implementing programmes with fragmented governance. The international experience shows TVET fund is one of the approaches to coordinate fragmented TVET stakeholders and enhance the quality of TVET. In absence of such an integrated TVET fund in Nepal, this paper urges for establishing TVET fund and sketches the possible approaches with reformed TVET structure. For this, first, we reviewed the literature particularly the perceived international practices of implementing TVET fund. Further, we arranged an interaction with TVET stakeholders and collected their views on the establishment of the TVET fund in Nepal. Based on findings of the research, the paper provides five possible models for establishing TVET fund mechanism in Nepal. All the models have their strengths and challenges, so it would be rational to adopt the idea of strengthening existing structure rather than making it stand alone. For this, a developing strong research and innovation, effective implementing body, and independent quality assurance and accreditation system is equally important for its effective implementation.